Investigation of the Mw 7.3 earthquake in Tonga Islands, Pacific Ocean, 11 November 2022 - Pirti, Atinc; Yucel, Mehmet Ali; Hosbas, Ramazan Gursel (INST GEOLOGY & GEOGRAPHY, 2024)
The Mw 7.3 Tonga earthquake occurred on 11 November 2022 at 19 degrees.288 S and 172 degrees.147 W. It was caused by reverse faulting in the outer rise of the Pacific Plate, about 75 km east of the Tonga Trench. We studied the Tonga earthquake on 11 November 2022 in order to detect a violent eruption of the Tonga submarine volcano in the South Pacific. Submarine volcano eruptions can displace seawater in a number of different ways, potentially triggering tsunamis. The Tonga subduction zone has the highest rate of plate convergence on Earth. It is one of the places with the most earthquakes. However, the recorded thrust events that can be placed with certainty on the plate boundary haven't been stronger than M 8.0, and the area's history suggests that there isn't much seismic coupling along the arc. The modelling of this earthquake based on the assumption that the fault plane dips to the west give dimensions of about 50 x 35 km, with most of the distance down -dipping from the hypocenter. In our study, we used the CSRS-PPP software to process TONGA station data using static and kinematic methods. This study shows the horizontal coordinate differences of the TONGA station (static -kinematic), which range from a few millimetres to about 40 centimetres.
Keywords: GNSS; Tonga earthquake; displacements; deformation; DEEP; ARC; Geology